The Vector of Institutional Development in Russia: From Quasi-Market to the Liberal Distribution - Ольга Эрнестовна Бессонова (Journal of Economic Sociology, 2010)
The results of transformation process in Russia came out to be just the opposite to the reformators’ expectations at the beginning of 1990s. That is why the government has changed the course of reforms and implemented the traditional for Russian economy practices the given mechanisms in the new forms. The general theory of institutional transformations gives another explanation towards what is going on. The explanation differs from the popular assumption of renaissance of plan economy and renewal of the institutions of power-ownership. According to this theory Russia has witnessed the creation of the «economy of the liberal distribution», the characteristics of which become the state contract and state order as modern forms of institutionalization of the “take-give” relations, state corporations become the basis for production function while the basic economic mechanism will be budget accounting